(3LGeY GdeHGOF hGdZGjGJs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI aEfi deG QCjJ cKjQkG GdfGS jNhVhf ai hVY GdBdGJ GdadcjI s
(3BNQgG (B:s
(3ZjQ hGVM s
(3JMJhi Ydi cKjQ ef GdQShe GdgfOSjI hGdLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B473 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B24 s
Keywords: (3Gdadcs